International networking guidelines for nurses - Gaisser, D'Arcy J. (2021)
Basic guidelines are necessary for international networking in nursing. This article outlines the benefits of and strategies for networking, highlights the social and behavioral considerations of social networking, and presents potential guidelines for further discourse.